Comparison of Behavior of Reinforced Concrete Dual-system Structure (Frame-Shear Wall) and Steel Dual-system Structure (Frame- Special Plate Shear Wall) in High Rise Building (Case Study: IT Mandiri Bumi Slipi Building) - Auliya Amir, Ahmad Yusron; Krisnamurti; Wiswamitra, Ketut Aswatama (Rekayasa Sipil, 2024)
Indonesia is vulnerable to earthquakes due to its location on the “Ring of Fire,” recent research highlights the potential for megathrust earthquakes off the southern coasts of Java and Sumatra. Researching earthquake-resistant building structures' behavior is very important to obtain a more effective and efficient structure. Materials, structural types, and forces such as dead loads, live loads, and earthquake loads influence the structural behavior of high-rise buildings. IT Mandiri Bumi Slipi building, with a height of 149.6 m and 32 floors, exhibits structural irregularities vulnerable to earthquakes. High-rise buildings require earthquake-resistant systems, such as dual-system structures incorporating frames and shear walls. This study compares the behavior of reinforced concrete and steel structures (special plate shear walls) in a 32-story building, focusing on structural weight, beam bending moment, base shear force, and seismic displacement. The analysis used ETABS software and LRFD principles, with spectrum response analysis for seismic loads. Results showed that the reinforced concrete model had seismic base shear forces of 21578.87 kN in the X direction and 21577.91 kN in the Y direction, with drifts of 276.664 mm in the X direction and 141.33 mm in the Y direction, and the largest beam bending moment of 6713.27 kN-m. The steel model shows seismic base shear forces of 10927.52 kN in the X direction and 10929.99 kN in the Y direction, with drifts of 250.31 mm in the X direction and 119.33 mm in the Y direction, and the largest beam bending moment of 4221.82 kN-m. Steel structures are lighter and more effective at resisting seismic loads than concrete, with a weight of 257801.8 kN versus 508305.6 kN and smaller drift and shear force. These findings serve as a reference for innovation in earthquake-resistant construction of high-rise buildings.